Assessing the Socio-Economic and Environmental Performance of Agroforestry Systems in Kalinchowk Rural Municipality, Nepal - Amgain, Ojaswee; Joshi, Murari Raj (Journal of the Institute of Agriculture and Animal Science, 2025)
Agroforestry plays an important role in supporting rural livelihoods and enhancing environmental resilience in Nepalese hill farming systems. This study assessed the socio-economic and environmental performance of major agroforestry systems in Kalinchowk Rural Municipality, Dolakha District, Nepal, with particular emphasis on household livelihood status, food sufficiency, and climate adaptation. The study was based on a household survey of 136 households selected through simple random sampling, complemented by key informant interviews, field observations, and meteorological data obtained from the Department of Hydrology and Meteorology. Socio-economic indicators included landholding, livelihood strategies, livestock ownership, household assets, and food sufficiency, while environmental parameters focused on perceived climatic changes, local environmental conditions, and agroforestry-related ecosystem services. Data were analyzed using descriptive statistics and chi-square tests in SPSS and MS Excel. The results show that agriculture remains the primary occupation for 69.85% of households, yet food sufficiency is low, with only 27.9% of households meeting annual food requirements from own production and 25.7% producing food for less than six months. Based on a composite livelihood assessment, most households fell into low (50.0%) and medium (19.9%) livelihood categories. The dominant agroforestry systems dominated in the study area were agri-silviculture (66.18%), agri-horti-silviculture (18.38%), silvi-pastoral systems (10.29%), and home gardens. A statistically significant association was observed between agroforestry system type and household food sufficiency (χ² = 24.16, p < 0.05), indicating better socio-economic performance and higher resilience among households practicing diversified systems, particularly agri-horti-silviculture and silvi-pastoral systems. Environmentally, 57.4% of households reported overall improvement in local environmental conditions, particularly in soil fertility and microclimate regulation. Despite these benefits, the performance of agroforestry systems is constrained by pest infestations, human–wildlife conflict, limited market access, and uneven institutional support, indicating the need for targeted technical extension, improved market linkages, inclusive support mechanisms, and the integration of agroforestry into local climate adaptation planning. Overall, the study indicates that agroforestry, especially agri-horti-silviculture offers balanced socio-economic and environmental benefits and represents a viable climate-smart land-use option for improving livelihood resilience and environmental sustainability in mid-hill and high-hill regions of Nepal.